PENGARUH CITRA MEREK DAN CITRA PENGECER TERHADAP RESPON MEREK DAN RESPON PENGECER MELALUI KEPUASAN MEREK DAN KEPUASAN PENGECER - Didit Darmawan; Pantja Djati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
This research tries to compare brand image electronic products and store image to brand responses and store responses through brand satisfaction and customer store- satisfaction. The dominating existence of brand image and store image where customers buy the product.The result of this research shows that brand satisfaction influence brand responses than customer store-satisfaction. The contribution of this research for managers is that positive store image and customer store- satisfaction doesn’t mean that customer will not switch to other store but brand image and customer satisfaction to brand potentially hold the brand switching intention.